Peningkatan Kapasitas Manusia Sebagai Fokus dari People Centered Development - Purwowibowo, Purwowibowo; Hendrijanto, Kris; Soelistijono, Pra Adi (Universitas Muhammadiyah Ponorogo, 2018)
This article discusses the development paradigm that focuses on humanÂ or people centered development. Many development paradigms have been applied in many developing countries, but the results have not been satisfactory. During this time the various paradigms emphasize economic growth, equity of development, and others, but the distortion of development appears everywhere. For example, development by emphasizes economic-growth was followed by massive environmental damage. In addition, poverty is still a portrait of people in developing countries, although the country is experiencing high economic growth. In realizing a prosperous society free of poverty, a new strategy or development paradigm that emphasizes its human factors are needed. In this case, this paradigm discusses the importance of the human element as the 'core' of development itself. If human beings are capable, have sufficient knowledge, adequate skills by themselves poverty will be reduced. Therefore, this paradigm more implies that is a 'capacity building ' of human beings so that it can become the subject of development and not just as an object of development themselves. Capacity building can be achieved through social development that emphasizes elements of education, knowledge, and skills so that they can try or do entrepreneurship and open their own job opportunities. Many cases, various development paradigms that emphasize economic growth are not able to absorb the available labor so that many are unemployed. With the ability of human or people, they have will be able to open their own business and do not depend on the provision of employment from the government. In the end they are able to alleviate self-poverty.